From Endorsement of Ambivalent Sexism to Psychological IPV Victimization: The Role of Attitudes Supportive of IPV, Legitimating Myths of IPV, and Acceptance of Psychological Aggression - Cinquegrana, Vincenza; Marini, Maddalena; Galdi, Silvia (Frontiers in Psychology, 2022)
Research on intimate partner violence (IPV) has recognized psychological abuse as a precursor of physical and sexual violence in intimate relationships. However, risk factors in predicting women’s psychological abuse victimization in such a context are still unclear. The goal of the present work was to investigate the role of ambivalent sexism on psychological IPV victimization, by taking into account in the same study the effect of three additional social-psychological factors: women’s i) attitudes supportive of IPV, ii) endorsement of legitimating myths of IPV, and iii) acceptance of psychological aggression in intimate relationships. A total of 408 Italian young women (Mage = 23.87; SD = 2.39) involved in non-marital heterosexual romantic relationships completed measures aimed at assessing i) hostile and benevolent sexism, ii) attitudes supportive of IPV, iii) legitimating myths of IPV, iv) prevalence of psychological abuse experienced within the last 12 months, and performed a task developed ad hoc to measure v) acceptance of psychological aggression in intimate relationships. Results showed that the effect of ambivalent sexism on participants’ prevalence of psychological abuse was mediated by the endorsement of attitudes supportive of IPV and legitimating myths of IPV, as well as by acceptance of psychological aggression. Findings are discussed based on literature about ambivalent sexism, and attitudes and beliefs about IPV.